VirF Relieves the Transcriptional Attenuation of the Virulence Gene icsA of Shigella flexneri Affecting the icsA mRNA–RnaG Complex Formation - Giangrossi, Mara; Giuliodori, Anna M.; Tran, Chi N.; Amici, Augusto; Marchini, Cristina; Falconi, Maurizio (Frontiers in Microbiology, 2017)
VirF is the master activator of virulence genes of Shigella and its expression is required for the invasion of the human intestinal mucosa by pathogenic bacteria. VirF was shown to directly activate the transcription of virB and icsA, which encode two essential proteins involved in the pathogenicity process, by binding their promoter regions. In this study, we demonstrate by band shift, enzymatic probing and cross-linking experiments that VirF, in addition to DNA, can also bind the icsA transcript and RnaG, an antisense non-coding small RNA that promotes the premature termination of icsA mRNA through a transcriptional attenuation mechanism. Furthermore, we show that VirF binds in vitro also other species of RNAs, although with lower specificity. The existence of VirF-RnaG and VirF-icsA mRNA complexes is confirmed in a pulldown assay carried out under experimental conditions that very close reproduce the in vivo conditions and that allows immobilized VirF to “fish” out RnaG and icsA mRNA from a total RNA extract. The VirF binding sites identified on both icsA mRNA and RnaG contain a 13 nucleotides stretch (5’-UUUUaGYcUuUau-3’) that is the RNA-converted consensus sequence previously proposed for the VirF-DNA interaction. Band-shift assays with a synthetic RNA molecule whose sequence perfectly matches the consensus indicate that this signature plays a key role also in the VirF-RNA interaction, in particular when exposed in a stem-loop structure. To further explore the icsA-RnaG-VirF regulatory system, we developed an in vitro test (RNA-RNA Pairing Assay) in which pairing between icsA mRNA and synthetic RNAs that reproduce the individual stem-loop motifs of RnaG, was analyzed in the presence of VirF. This assay shows that this protein can prevent the formation of the kissing complex, defined as the initial nucleation points for RNA heteroduplex formation, between RnaG and icsA mRNA. Consistently, VirF alleviates the RnaG-mediated repression of icsA transcription in vitro. Therefore VirF, by hindering the icsA transcript-RnaG interaction, exhibits an activity opposed to that usually displayed by proteins, which generally assist the RNA-RNA interaction; this quite uncommon and new function and the regulatory implications of VirF as a potential RNA-binding protein are discussed.